Antibacterial effects of the ethanolic leave extracts of Musa paradisiaca, Musa acuminata and Musa sapientum against MRSE and MSSE - Virusha, Nimalan; Lalita Ambigai, Sivasamugham; Geetha, Subramaniam (INTI International University, 2019)
The extracts from the stem, fruit peels and leaves of banana plants are being investigated for their antibacterial effects. The number of effective drugs against resistant bacteria including methicillin-resistant Staphylococcus epidermidis are reducing with time. Thus far, there are no studies done on the antibacterial effects of the ethanolic leave extracts of banana leaves against MRSE. Thus, the aim of this study was to investigate the antibacterial effects of 80% ethanolic leave extracts of Musa paradisiaca, Musa acuminata and Musa sapientum against MRSE. The ethanolic leave extracts were extracted and concentrated using a soxhlet extractor and a rotary evaporator. The antibacterial effects of the extracts against the isolates were analyzed using the agar well diffusion assay. The ethanolic extracts of M. paradisiaca showed the highest zone of inhibition of 30.3 mm against MRSE isolate S15B/A. Inhibition was also observed with methicillin-sensitive S. epidermidis (MSSE). Although there were differences in the diameters of the zones on the inhibition, the post-hoc test revealed that the extracts of M. paradisiaca and M. acuminata were equally effective (p ≤ 0.05) in inhibiting the growth of MRSE isolates at 2.86g/mL and 3.33g/mL concentration respectively. These extracts also produced significantly larger zones of inhibition compared to clindamycin. The presence of salvipisone and aethiopinone diterpenoids in the extracts of M. paradisiaca and M. acuminata could be the reason for the inhibition against MRSE. These findings strongly suggest that the ethanolic leave extracts of Musa paradisiaca and Musa acuminata have the potential to be developed as effective antibacterial agents against MRSE and MSSE.